A profile of spa-goers in the U.S. luxury hotels and resorts: a posteriori market segmentation approach. Issue 8 (17th November 2019) - Huh, Chang; Lee, Myong Jae; Lee, Soojin
ABSTRACT: A spa is one amenity that enhances the overall experience of hotel guests, which in turn, generates significant revenue for luxury hotels and resorts in the U.S. Little research has examined spa-goer motives and whether spa-goers can be segmented both for service value and effective marketing mix. This study segmented spa guests in luxury hotels and resorts by motivation and compared them using socio-demographic characteristics and past experiences. In this study, we performed a series of multivariate statistical analyses for 309 survey respondents in the U.S. to segment spa-goers staying in luxury hotels and resorts. Pleasure pursuers find spas more attractive if the spas have entertainment or they can visit with friends or purchase spa products. Healing pursuers visit spas to ease emotional stress and spiritual fatigue. Relaxation pursuers tend to use spa treatments as a relief from daily routines. The implications for luxury spa marketing strategies are discussed.